Should the Government Be in the Banking Business? The Role of State-Owned and Development Banks - Eduardo Levy Yeyati; Alejandro Micco; Ugo Panizza (Inter-American Development Bank, Research Department, 2004)
This paper surveys the theoretical and empirical literature on the role of state-owned banks and also presents some new results and a robustness analysis. The paper shows that state-owned banks located in developing countries have fiscal costs because they are characterized by lower returns than comparable privately owned banks (on the other hand, there is no evidence that state-owned banks located in industrial countries are less profitable than their private counterparts). We then point out that this evidence cannot be used as an argument against the existence of state-owned banks, as this low profitability might stem from state-owned banks activity on projects characterized by low private sector investment and high social return. While we find no evidence that the presence of state-owned banks promotes economic growth or financial development, we also find that the evidence that state-owned banks lead to lower growth and financial development is not as strong as previously thought.
Keywords: G21; H11; O16; 330; Banking; Privatization; State-owned banks; Financial development; Latin America; Öffentliche Bank; Privatisierung; Lateinamerika